MARKETING ANALYSIS MASAMO CATFISH AT SUKAS FISH FARM EAST UNGARAN DISTRICT, SEMARANG REGENCY - Anggit Ribowo; Sulis Wati; Karyadi Karyadi (Jurusan Perikanan dan Kelautan, 2023)
This study aims to determine marketing channels, the amount of margin and the farmer's share and the marketing efficiency masamo catfish in the fish farmer group sukas fish. The method used in this research is descriptive analysis method, data and literature studies. Based on the analysis results obtained in a research note that the marketing catfish masamo in a group of fish farmers efficiently halcyon sukas. It is based on the analysis of the purchase price, selling price and profit earned marketing agencies involved. The efficiency value of each institution, namely marketing, traders and retailers 0.051 0.038. There are three masamo marketing channel catfish in the fish farmer groups mina tranquility. Channel 1:farmers and consumers. Channel 2: growers, retailers and end customers. Channel 3: farmers, traders, retailers and end customers. The amount of margin cultivators (Rp.2.000), collector (Rp.3.500) and retailers (Rp.4.500). Farmer's share value on channel 1 (100%), channel 2 (82.05%) and channel 3 (81,25%).